HCI International 2011 Posters extended abstracts international conference, HCI International 2011, Orlando, FL, USA, July 9-14, 2011, proceedings. Part I - International Conference on Human-Computer Interaction 2011 Orlando, Fla.); Stephanidis, Constantine; SpringerLink (Online service). (Berlin New York Springer, 2011)
This two-volume set CCIS 173 and CCIS 174 constitutes the extended abstracts of the posters presented during the 14th International Conference on Human-Computer Interaction, HCII 2011, held in Orlando, FL, USA in July 2011, jointly with 12 other thematically similar conferences. A total of 4039 contributions was submitted to HCII 2011, of which 232 poster papers were carefully reviewed and selected for presentation as extended abstracts in the two volumes.
Electronic reproduction.
Keywords: Human-computer interaction -- vCongresses; Electronic books